Emerging investigator series: bacterial opportunistic pathogen gene markers in municipal drinking water are associated with distribution system and household plumbing characteristics. Issue 11 (7th October 2020) - Haig, Sarah-Jane; Kotlarz, Nadine; Kalikin, Linda M.; Chen, Thomas; Guikema, Seth; LiPuma, John J.; Raskin, Lutgarde
Abstract : Municipally-treated drinking water (DW) is a potential source of exposure to bacterial opportunistic pathogens (OPs), which can cause infection in susceptible individuals. Abstract : Municipally-treated drinking water (DW) is a potential source of exposure to bacterial opportunistic pathogens (OPs), which can cause infection in susceptible individuals. In this study, we used quantitative PCR to determine concentrations of two bacterial species ( Pseudomonas aeruginosa and Stenotrophomonas maltophilia ) and three genera containing OPs (nontuberculous mycobacteria [NTM], Achromobacter spp., and Burkholderia spp.) in water and faucet aerator biofilm samples collected from 15 homes serviced by one DW treatment plant and distribution system. DNA from all five groups was detected in all samples. In addition to quantifying OP gene markers, we measured 15 water quality parameters and generated linear mixed-effect models, demonstrating that dissolved iron concentration was positively associated with the concentration of each bacterial group. Distribution system associated characteristics such as disinfectant concentration, water age, and pressure zone also had a significant association (individually and collectively) with OP abundance. Home specific factors influenced the abundance of some OPs. Specifically, water in newer homes and in homes with plastic plumbing contained higher concentrations of S. maltophilia and Achromobacter spp., respectively. Collectively, these findings provide insights into factors that may impact the abundance of OPs throughout the distribution system and building plumbing transect and will aid in the development of mitigation strategies to reduce waterborne opportunistic infections.